Motivation Toward Plugin Hybrid Electric Vehicles to Reduce Transport Carbon Emission in Malaysia: A Conceptual Paper - Abbasi, H.A. (Springer Science and Business Media B.V., 2021)
The transport sector is the leading source of growing greenhouse gas (GHG) emissions globally. Malaysia ranks 26th globally in carbon emission, and the transport sector is the second most GHG emitter after electricity generation. Vehicles produce 85.2 of emissions and 59 of emissions come from private vehicles in Malaysia, and the best possible way to reduce transport emissions is the diffusion of Plugin Hybrid Electric Vehicles (PHEVs). The PHEVs operate on the electric battery as the battery power depletes, then start operating on a conventional engine. Consumers are observed not aware of these vehiclesâ features, and their motivation is not efficient that is why the purchase of the electric vehicle is very low. Social media is a very effective tool of marketing to aware consumers, worldwide more than 51 on earth use social media, and in Malaysia, almost 81 population is active social media users. Social media can play a significant role in enhancing motivation. The study's conceptual framework is thoroughly based on secondary data that combined the incoherent frameworks proposed by different authors into a single study. This study proposed the factors that can motivate and encourage consumers to purchase these vehicles. It will also be helpful for the government to reduce the carbon emission level in pursuing Carbon Neutral Nation 2050 and Greentech Master Plan 2030 target. Â© 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.